Correlates and determinants of nutritional status of adolescent girls: a comparative study among government and private schools - Kokiwar, Prashant R.; Reddy, P. Yadu Vamshi; Nikitha, P.; Rajitha, P.; Angeline, P. Nissi; Preethi, V.; Navya, P.; Chitra, R. Sai; Sameera, R. Hima (International Journal Of Community Medicine And Public Health, 2018)
Background: Under nourished adolescent girls are more likely to give birth to malnourished child when they become pregnant and deliver. Hence their nutritional status is of much more importance. Objectives were to study the nutritional status of adolescent girls, to study the correlates and determinants of nutritional status and compare it between government and private schools. Methods: A school based cross sectional study was carried out for a period of three months. This study was comparative in nature, comparing the adolescent girls from government and private schools. It was possible to study 74 and 97 adolescent girls from government and private schools respectively. Anthropometric measurements were recorded using standard guidelines. Results: There were only 4 cases (5.4%) of underweight and only 3 cases (4.1%) in government school. Similarly there was only one case (1.03%) of underweight and only 7 (7.2%) of the cases in the private school. The mean height was significantly less among the children from government school compared to the private school. But there was no difference between the mean weight and BMI of children from two schools. Conclusions: Prevalence of overweight and obesity was low in the present study. It was not found to be associated with education and occupation of parents and type of family.